2008
DOI: 10.1111/j.1530-0277.2008.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of ADH and ALDH Gene Variants With Alcohol Drinking Habits and Cardiovascular Disease Risk Factors

Abstract: In this Caucasian population sample, we found evidence to support that genetic variation in ethanol metabolism may influence drinking habits, but no statistically significant gene-environment interactions. More large-scale epidemiologic studies are needed to confirm theses results and to further investigate genetic susceptibility to the effects of alcohol drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 58 publications
3
51
3
Order By: Relevance
“…A study using crude lysate from HuH7 hepatoma cells reported that mitochondrial ALDH1B1 contributed to the oxidation of short-chain aldehydes including acetaldehyde and propionaldehyde, implying a role for ALDH1B1 in ethanol metabolism (Stewart et al, 1995). In agreement with this report, two recent large population-based studies identified two ALDH1B1 variants that were associated with drinking behavior (A69V) and alcohol-induced hypersensitivity (A86V) in whites (Husemoen et al, 2008;Linneberg et al, 2010). These findings strongly suggest that ALDH1B1 enzyme may be involved in ethanol detoxification and modifications in this enzyme may contribute to alcohol-related diseases.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…A study using crude lysate from HuH7 hepatoma cells reported that mitochondrial ALDH1B1 contributed to the oxidation of short-chain aldehydes including acetaldehyde and propionaldehyde, implying a role for ALDH1B1 in ethanol metabolism (Stewart et al, 1995). In agreement with this report, two recent large population-based studies identified two ALDH1B1 variants that were associated with drinking behavior (A69V) and alcohol-induced hypersensitivity (A86V) in whites (Husemoen et al, 2008;Linneberg et al, 2010). These findings strongly suggest that ALDH1B1 enzyme may be involved in ethanol detoxification and modifications in this enzyme may contribute to alcohol-related diseases.…”
Section: Introductionsupporting
confidence: 79%
“…Although approximately 50% of Asians are carriers of this variant, it is nearly absent in whites. Recent studies have identified the genetic determinants of drinking behavior and alcohol hypersensitivity among whites to be polymorphisms in the human ALDH1B1 gene, which encodes another mitochondrial ALDH isoenzyme (Husemoen et al, 2008;Linneberg et al, 2010). These studies and others (Stewart et al, 1995) are suggestive of a potentially important role of ALDH1B1 in the metabolism of acetaldehyde, but more direct confirmation remains to be established.…”
Section: Discussionmentioning
confidence: 92%
“…The two main polymorphisms of ADH1C, the Arg272Gln and Ile350Val have an almost complete linkage between each other, as it was expected from previous studies [34]. However, the results regarding the effect of these mutations are not so obvious among Caucasians.…”
Section: Discussionmentioning
confidence: 42%
“…An alternative explanation for the association between FLG mutations and alcohol sensitivity could be that FLG mutation carriers drink more alcohol to suppress itching in the skin. As expected for a Caucasian population,we have previously reported that the ALDH2 487lys variant known to be strongly related to alcohol sensitivity and drinking in Asians is extremely rare in our background population [43], and other less strong genetic variants may play a role in alcohol sensitivity.…”
Section: Discussionmentioning
confidence: 87%